(untitled) (KIUT Publication, 2025)
This article analyzes the relationship between two significant trends in the global economy today: the growing importance of services and the increasing relevance of environmental issues. There are causal links between these two processes, as the green economy provides new opportunities for the development of trade in services, while the expansion of trade simultaneously helps address issues related to climate change and environmental protection.